Perceived stigma of HIV patients receiving task-shifted primary care service and its relation to satisfaction with health service: HIV stigma in task-shifted ART service - Aung, Myo Nyein; Moolphate, Saiyud; Kitajima, Tsutomu; Siriwarothai, Yaowaluk; Takamtha, Piyaporn; Katanyoo, Chitima; Okamura, Hiroshi; Field, Malcom; Noyama, Osamu; Deerojanawong, Jitladda; Klinbuayaem, Virat (The Journal of Infection in Developing Countries, 2017)
Introduction: HIV stigma is the remaining challenge to end the global epidemics of HIV. Whether stigma may form a barrier to the provision of ART within the community-based, primary care setting was not studied yet. Therefore, this study intended (1) to compare the levels of ‘perceived stigma’ in PLHIV attending district hospital and primary care units (PCUs), and (2) to measure the relation between HIV stigma and the satisfaction of patients with their health service. Methodology: In this cross-sectional study, two matched PLHIV attending district hospitals were recruited for every PLHIV attending a PCU, within a pilot project, until the end of 2014. 198 informed and consented participants were recruited. We used validated Thai version instruments to measure the levels of ‘perceived stigma’ and ‘internal shame’ and the Patient Satisfaction Questionnaire 18 (PSQ18) to measure patients’ satisfaction with the health service. Analysis applied MANOVA and multivariate robust regression. Results: The level of ‘perceived stigma’ and ‘internal shame’ levels were not significantly different between district hospitals attendants and PCU attendants (P>0.05 MANOVA). Moreover, the more patients were satisfied with the health service, the less likely to have ‘perceived stigma’ (β -5.9, 95% confidence interval -7.7 to -4.1) and ‘internal shame’ (β -5.7, 95% CI -8.3 to -3.2), P<0.001). Conclusions: HIV associated stigma would be minimized through the attempt to promote PLHIV’s satisfaction with ART service. There is ample role of health professional education and training to improve patients’ satisfaction. It may contribute to the aim of zero discrimination.